##### (a) We can expand log x5y z to get log5(xy)−log5(z) Incorrect: Your answer

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet \$5

(a) We can expand
log
 x5y z
to get
log5(xy)−log5(z)

.

(b) We can combine

 5 log x + log y − log z to get .
Oct 16th, 2017

We just need to use the following logaritmic properties:

1) log(AB) = log(A) + log(B)

2) Log(A/B) = log(A) - log(B)

3) Log(x^n) = n*log(x)

Part a

log(x^5y/z) = log(x^5y) - log(z) .................... See property 2

log(x^5y) - log(z) = log(x^5) + log(y) - log(z) ........................ See property 1

log(x^5) + log(y) - log(z) = 5log(x) + log(y) - log(z) ............... See property 3

Final answer: We can expand log(x^5y/z) to get:  5log(x) + log(y) - log(z)

Part b

5log(x) + log(y) - log(z) = log(x^5) + log(y) - log(z) ................ See property 3

log(x^5) + log(y) - log(z) = log(x^5y) - log(z) ........................... See property 1

log(x^5y) - log(z) = log(x^5y/z) ................................................. See property 2

Final answer: We can combine 5log(x) + log(y) - log(z) to get:  log(x^5y/z)

Jul 17th, 2015

...
Oct 16th, 2017
...
Oct 16th, 2017
Oct 17th, 2017
check_circle